2021
DOI: 10.1042/cs20210198
|View full text |Cite
|
Sign up to set email alerts
|

Glycoursodeoxycholic acid ameliorates diet-induced metabolic disorders with inhibiting endoplasmic reticulum stress

Abstract: Recent studies reveal that bile acid metabolite composition and its metabolism are changed in metabolic disorders, such as obesity, type 2 diabetes and metabolic associated fatty liver disease (MAFLD), yet its role and the mechanism remain largely unknown. In the present study, metabolomic analysis of 163 serum and stool samples of our metabolic disease cohort was performed and we identified glycoursodeoxycholic acid (GUDCA), glycine-conjugated bile acid produced from intestinal bacteria, were decreased in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
(65 reference statements)
4
8
0
Order By: Relevance
“…It has been shown that taurochenodeoxycholic acid (sodium salt) is negatively correlated with PPARγ, 47 which is known to be a major regulator of adipogenesis and insulin resistance, 48 and that changes in the taurochenodeoxycholic acid (sodium salt) content are closely related to PPARγ, affecting adipogenesis and insulin resistance., and our results also showed that HFD affected glucose tolerance and insulin resistance, and could significantly increase the expression of PPARγ (Fig. S3A †); while glycoursodeoxycholic acid could improve HFD-induced insulin resistance and hepatic steatosis, 49 and hypotaurine, a precursor of taurine, promoted fat metabolism and reduces fat accumulation. 50 Further, 9-KODE is a derivative of linoleic acid; while acetoacetate stimulates triacylglycerol synthesis, and these changes in metabolites responding to lipid synthesis and metabolism are consistent with the embodiment of our present findings.…”
Section: Discussionsupporting
confidence: 65%
“…It has been shown that taurochenodeoxycholic acid (sodium salt) is negatively correlated with PPARγ, 47 which is known to be a major regulator of adipogenesis and insulin resistance, 48 and that changes in the taurochenodeoxycholic acid (sodium salt) content are closely related to PPARγ, affecting adipogenesis and insulin resistance., and our results also showed that HFD affected glucose tolerance and insulin resistance, and could significantly increase the expression of PPARγ (Fig. S3A †); while glycoursodeoxycholic acid could improve HFD-induced insulin resistance and hepatic steatosis, 49 and hypotaurine, a precursor of taurine, promoted fat metabolism and reduces fat accumulation. 50 Further, 9-KODE is a derivative of linoleic acid; while acetoacetate stimulates triacylglycerol synthesis, and these changes in metabolites responding to lipid synthesis and metabolism are consistent with the embodiment of our present findings.…”
Section: Discussionsupporting
confidence: 65%
“…[ 41 ] GUDCA was also confirmed to be decreased in both serum and fecal samples in patients with hyperglycemia, and supplementation of GUDCA can ameliorate HFD‐induced insulin resistance and hepatic steatosis. [ 45 ] Hence, we proposed that the TG‐lowering effect of ER peptides can attribute to modulation of BA signaling by these peptides. In order to validate this hypothesis, we further measured the BAs profiling in feces.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, as a conserved adaptive mechanism in response to ER dysfunction, ER-unfolded protein response (UPRer) has been found to be involved in the regulation of CMs assembly [ 13 , 16 ], although the relevant mechanism remains unresolved. Meanwhile, multiple investigators suggested HFD is the most common inducement to UPRer [ 17 , 18 ], as seen in our previous study in fish [ 19 ]. However, few studies regarding the mechanism behind HFD-induced UPRer impairing CMs assembly and secretion have been reported.…”
Section: Introductionmentioning
confidence: 69%